Light, Ethylene and Auxin Signaling Interaction Regulates Carotenoid Biosynthesis During Tomato Fruit Ripening - Cruz, Aline Bertinatto; Bianchetti, Ricardo Ernesto; Alves, Frederico Rocha Rodrigues; Purgatto, Eduardo; Peres, Lazaro Eustaquio Pereira; Rossi, Magdalena; Freschi, Luciano (Frontiers in Plant Science, 2018)
Light signaling and plant hormones, particularly ethylene and auxins, have been identified as important regulators of carotenoid biosynthesis during tomato fruit ripening. However, whether and how the light and hormonal signaling cascades crosstalk to control this metabolic route remain poorly elucidated. Here, the potential involvement of ethylene and auxins in the light-mediated regulation of tomato fruit carotenogenesis was investigated by comparing the impacts of light treatments and the light-hyperresponsive high pigment-2 (hp2) mutation on both carotenoid synthesis and hormonal signaling. Under either light or dark conditions, the overaccumulation of carotenoids in hp2 ripening fruits was associated with disturbed ethylene production, increased expression of genes encoding master regulators of ripening and higher ethylene sensitivity and signaling output. The increased ethylene sensitivity observed in hp2 fruits was associated with the differential expression of genes encoding ethylene receptors and downstream signaling transduction elements, including the downregulation of the transcription factor ETHYLENE RESPONSE FACTOR.E4, a repressor of carotenoid synthesis. Accordingly, treatments with exogenous ethylene promoted carotenoid biosynthetic genes more intensively in hp2 than in wild-type fruits. Moreover, the loss of HP2 function drastically altered auxin signaling in tomato fruits, resulting in higher activation of the auxin-responsive promoter DR5, severe down-regulation of AUXIN/INDOLE-3-ACETIC ACID (Aux/IAA) genes and altered accumulation of AUXIN RESPONSE FACTOR (ARF) transcripts. Both tomato ARF2 paralogues (Sl-ARF2a and SlARF2b) were up-regulated in hp2 fruits, which agrees with the promotive roles played by these ARFs in tomato fruit ripening and carotenoid biosynthesis. Among the genes differentially expressed in hp2 fruits, the additive effect of light treatment and loss of HP2 function was particularly evident for those encoding carotenoid biosynthetic enzymes, ethylene-related transcription factors, Aux/IAAs and ARFs. Altogether, the data uncover the involvement of ethylene and auxin as part of the light signaling cascades controlling tomato fruit metabolism and provide a new link between light signaling, plant hormone sensitivity and carotenoid metabolism in ripening fruits.